2010
DOI: 10.2174/187152410790780145
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Cannabinoid CBII Receptor Agonists for the Treatment of Central Neuropathies

Abstract: Two cannabinoids receptors have been characterised in mammals; cannabinoid receptor type 1 (CBI) which is ubiquitous in the central nervous system (CNS), and cannabinoid receptor type 2 (CBII) that is expressed mainly in immune cells. Cannabinoids have been used in the treatment of nausea and emesis, anorexia and cachexia, tremor and pain associated with multiple sclerosis. These treatments are limited by the psychoactive side-effects of CBI activation. Recently CBII has been described within the CNS, both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 206 publications
(367 reference statements)
2
15
0
Order By: Relevance
“…Among the proposed mechanisms of cannabinoid-receptor mediated neuroprotection, two are particularly relevant for the neurotoxicity caused by alcohol dependence and withdrawal: the inhibition of the presynaptic release of glutamate [16] and the inhibition of NMDA-induced Ca 2+ influx [17]. It appears well-demonstrated that CB1 receptors are involved in these two neuroprotective properties of cannabinoid agonists and although HU-210 is a non-selective cannabinoid agonist, we assume that, in our experiments, HU-210 preferentially acts through the activation of CB1 receptors because -consistent with the suggestion that CB2 receptors are essentially present in glial cells [18] and considering the high purity of our neuronal cultures (thanks to the use of an anti-mitotic agent)- no mRNA encoding for CB2 receptors were detected in our cultures (data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…Among the proposed mechanisms of cannabinoid-receptor mediated neuroprotection, two are particularly relevant for the neurotoxicity caused by alcohol dependence and withdrawal: the inhibition of the presynaptic release of glutamate [16] and the inhibition of NMDA-induced Ca 2+ influx [17]. It appears well-demonstrated that CB1 receptors are involved in these two neuroprotective properties of cannabinoid agonists and although HU-210 is a non-selective cannabinoid agonist, we assume that, in our experiments, HU-210 preferentially acts through the activation of CB1 receptors because -consistent with the suggestion that CB2 receptors are essentially present in glial cells [18] and considering the high purity of our neuronal cultures (thanks to the use of an anti-mitotic agent)- no mRNA encoding for CB2 receptors were detected in our cultures (data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…Rivers and Ashton (2010) stated that this finding is not unexpected because microglial cells are resident immune cells of the CNS derived from the same lineage as peripheral immune cells. Microglial cell activation releases several mediators of pain, including TNF␣, IL-1, and IL-6 (Shan et al 2007), and various other substances that increase nociceptive transmission (Watkins et al 2001;Waltkins and Maier 2003;DeLeo et al 2004).…”
Section: Notementioning
confidence: 90%
“…Cannabinoid compounds, plant-derived, synthetic and endogenous, are well known to elicit potent effects on inflammation, both peripherally and centrally. The presence of CB 2 receptors on glia and neurons in the brain, has prompted several groups to investigate the role of this receptor in neuroinflammation and neuroprotection, a topic which has been covered in detail by several recent reviews [43,44,45,46,47,48,49]. This body of evidence suggests that CB 2 receptor activation elicits glial-dependant anti-inflammatory effects, thereby reducing neuroinflammation associated with several neurodegenerative diseases.…”
Section: Neuroinflammation and Cb2 Receptorsmentioning
confidence: 99%
“…Similarly, GlaxoSmithKline have also completed Phase 2 clinical trials evaluating the effects of the selective CB 2 agonist GW842166, in osteoarthritis [41] and dental pain [42], although the results of these studies have not been published to date. Identification of CB 2 receptors in the central nervous system has also led to increasing investigation into its involvement in neuroimmunological and neurodegeneratative disorders, topics which have been covered in detail by several recent reviews [43,44,45,46,47,48,49,50]. The present review will provide an overview of the evidence demonstrating the presence of functional CB 2 receptors in the brain, the role of this receptor in neurophysiology and highlight the potential involvement of these receptors in neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%